Research progress on the integrative nursing for patients with chronic bronchitis in China (中西医结合护理在慢性支气管炎患者中的研究进展) - SUN Ce (孙策) (中西医结合护理)
Integrative nursing is a nursing model that combines the advantages of western and Traditional Chinese Medicine (TCM) nursing. This paper compares the differences between the TCM and Western medicine in the nursing of patients with chronic bronchitis, and exhibits the advantages of integrative nursing in controlling the progress of chronic bronchitis and focuses on the clinical application progress of integrative nursing in chronic bronchitis. Meanwhile, this paper also discusses the limitations, necessity and feasibility of the development and clinical practice of integrative nursing in China. (中西医结合护理是一种能够兼具西医护理对症准、见效快和中医护理根治病因、长期养护为特点护理模式。本文比较了中医、西医护理在慢性支气管炎患者护理上的差异, 阐述了中西医结合护理在控制慢性支气管炎患者病情进展上的优势, 详细并重点的说明了中西医结合护理在慢性支气管炎疾病上的临床应用进展, 以其为进一步完善中西医结合护理在临床上应用规范提供参考。)